(untitled) (Annals of Medical Research, 2021)
Aim: Seen frequently in young women, mastodynia impairs patients’ quality of life by raising worries about breast cancer.Material and Methods: In this study, 101 mastodynia patients under 35 years of age who presented to our clinic between July 2018 and July 2019 were reviewed retrospectively. The data collected included age, family history of breast cancer, time passed since the onset of mastodynia, localization, relationship with menstrual cycles, physical examination findings, regularity of menstruation, breast USG results, number of outpatient clinic revisits, diagnoses made for those who were resistant to treatment upon a psychiatric examination, and general follow-up outcomes.Results: The ages of the patients ranged between 19 and 35 years. A family history of breast cancer was present in 10%. Mastodynia was cyclic in 70%. In breast USG, 58.4% of the patients had signs of BI-RADS 1. Those who had BI-RADS 2 and BI-RADS 3 were followed up for an average of 7 months and no malignancy developed. A psychiatric examination was administered to patients who were resistant to treatment and 23 (22.8%) were diagnosed with various psychiatric disorders, mostly with anxiety disorder and panic disorder. Specific treatments were given to these patients and mastodynia alleviated or disappeared in half of them.Conclusion: The incidence of breast cancer is very low in mastodynia patients under the age of 35 years. The main treatment approach for these patients should be to eliminate their worries about cancer and to relieve them mentally. A psychiatric examination can be useful in treatment-resistant cases.